A Framework of Software Defect Prediction By Data Mining Techniques Using Historical Data Set and Intelligent Agents - Bondyopadhyay, Amitava (International Journal of Computer Sciences and Engineering, 2025)
Defect prediction for a software system is a technique that is used extensively nowadays to predict defects from historical database. But only a good data mining model is not enough to extract defect from software bug record. Intelligent agents are helpful in this case by making the decision process easier at some point. This paper describes frame work to generate software defect from the historical database and also propose one algorithm that is used find policy to forecast software defects efficiently than the current methods